ADOLESCÊNCIA: TEMPO DE ESPERA - Kryzozun, Lucas Cavalheiro; Tres, Jenaína; De Melo, Renan Martins; Dos Santos, Alexa Fagundes (Salão do Conhecimento, 2018)
Projeto de Iniciação Científica realizado no curso de Psicologia da Unijuí